Right to reply: Power and ethics in humanities research: A response to Stolp - Lyn Horn; Anton van Niekerk; Therina Theron; Leslie Swartz; Lesley le Grange (Acta Academica, 2016)
In the spirit of open engagement we respond to the article published in the last issue of Acta Academia by Mareli Stolp entitled “Report to the Academy: Power and ethics in humanities research”. This article raises many important issues but also requires, in our opinion, the presentation of an alternative perspective or narrative of the events chronicled. In responding to Stolp’s discussion of this incident, four aspects will be discussed: (1) the conceptual delineation of the scope of research misconduct, research integrity and research ethics, (2) Research ethics and integrity at   Stellenbosch University and the allegation that it used as a managerial tool to supress academic freedom (3) the investigation process itself, and finally (4) the question of innocence or guilt. In conclusion we believe that a limited knowledge and understanding of research ethics particularly as it applies to autoethnography, a context of intra-departmental conflict and a specific historical context led to the conflation of numerous issues and to this series of events.